2005
DOI: 10.1111/j.1745-6584.2005.0042.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mineral Fouling on Hydraulic Behavior of Permeable Reactive Barriers

Abstract: This paper describes reactive transport simulations conducted to assess the impact of mineral fouling on the hydraulic behavior of continuous-wall permeable reactive barriers (PRBs) employing granular zero-valent iron (ZVI) in carbonate-rich alluvial aquifers. The reactive transport model included a geochemical algorithm for simulating corrosion and mineral precipitation reactions that have been observed in ZVI PRBs. Results of simulations show that porosity and hydraulic conductivity of the ZVI decrease over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 41 publications
0
69
0
Order By: Relevance
“…Several researchers (Karvonen 2004;Komnitsas et al 2007;Li and Benson 2005;Liang et al 2003;McMahon et al 1999;Puls et al 1999a;Sarr 2001;Vogan et al 1999;Yabusaki 2001) have reported that armouring on the surface of reactive materials and chemical clogging of pores, by precipitated compounds during chemical reactions inside the PRB, decrease the long-term performance parameters such as reactivity, porosity and permeability. Significant concerns relating to precipitation of iron and aluminium oxides and hydroxides also exist in alkaline PRBs with acidic groundwater in ASS terrain because their solubilities are pH-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers (Karvonen 2004;Komnitsas et al 2007;Li and Benson 2005;Liang et al 2003;McMahon et al 1999;Puls et al 1999a;Sarr 2001;Vogan et al 1999;Yabusaki 2001) have reported that armouring on the surface of reactive materials and chemical clogging of pores, by precipitated compounds during chemical reactions inside the PRB, decrease the long-term performance parameters such as reactivity, porosity and permeability. Significant concerns relating to precipitation of iron and aluminium oxides and hydroxides also exist in alkaline PRBs with acidic groundwater in ASS terrain because their solubilities are pH-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…This structuring allows the ZVI to actively remove divalent and trivalent cations from the water [2] and convert them into effective catalysts [133]. Both oxygen evolution [26,70,134] and hydrogen evolution [1,70,71,105,108,109,[134][135][136][137][138] have been associated with the placement of ZVI in water.…”
Section: F2 Fe Catalystmentioning
confidence: 99%
“…Some PRB designers have attempted to overcome the adverse effect of permeability destruction by creating a PRB with a higher initial permeability than the surrounding aquifer [108]. Porosity, φ, reduction in a ZVI PRB can be modelled by assuming a pseudo-first order corrosion reaction and by using hydraulic conductivity (K c ) to represent permeability (k p ) where [109]:…”
Section: E41 Porosity Reductionmentioning
confidence: 99%
“…Accordingly, the precipitation of iron corrosion products and other secondary minerals is regarded as perturbing side effect yielding reactivity and porosity loss [2,14,16,17]. Accordingly, the design of a PRB requires profound knowledge of local water flow velocity (residence time), aquifer porosity, influent contaminant concentration.…”
Section: Current Design Approach To Limit Fe 0 Prb Cloggingmentioning
confidence: 99%
“…gravel, pumice, sand) [2,14]. Because of the volumetric expansive nature of the process of iron corrosion [15], the porosity of the filtrating systems certainly decreases with increasing service life, possibly yielding complete permeability loss system (filter clogging) [16,17]. The filling of the pore volume by corrosion products is necessarily coupled with improved size exclusion capacity.…”
Section: Introductionmentioning
confidence: 99%